ASEAN Progress Towards Sustainable Development Goals and The Role of the IMF. (Policy Papers; Policy Paper, 2018)
Attainment of the Sustainable Development Goals (SDGs) will require that the Association of Southeast Asian Nations (ASEAN) countries continue their considerable past achievements. The Millennium Development Goals-which were to have been met by 2015-helped focus attention on achieving progress towards poverty reduction, better health outcomes, and improvements in education in the ASEAN developing countries. The 17 SDGs-adopted in 2015 and to be met by 2030-cover a wider set of interlinked development objectives, such as inclusion and environmental sustainability, which are important for all countries, including all ASEAN member countries. ASEAN countries have made significant progress in improving incomes and economic opportunities, including for women, and reducing poverty since 2000. Reflecting the economic dynamism of the region, strong income growth, structural transformation, and infrastructure improvements continue to support sustainable development in ASEAN. With continued income growth and strong policy efforts, most ASEAN countries are on track to eradicate absolute poverty by 2030, a major milestone. Also, several ASEAN countries already do relatively well in terms of gender equality. As a result, given support from continued income gains, economic welfare in ASEAN countries is expected to continue converging towards advanced Asia levels. Ensuring more inclusive and environmentally sustainable growth presents a key challenge for ASEAN. Despite some progress, income inequality remains relatively high in several countries and the shift towards manufacturing strains environmental sustainability. These challenges hamper ASEAN welfare convergence relative to advanced Asia. Policies to close these gaps in sustainable development can lead to significant gains. For the lower-middle-income ASEAN countries, in particular, more determined policy efforts are needed to improve infrastructure, as well as health and education outcomes. Remaining sustainable development challenges call for comprehensive, country-specific SDG strategies formulated in the context of national development plans and close monitoring through the voluntary review process. Pursuing sustainable development entails sizeable spending needs. Estimates for Indonesia and Vietnam, the two cases studies considered in this paper, show that reaching the level of best performers in their income group in infrastructure, health, and education by 2030 could entail an additional cost of 5 1\2 -6 1\2 percent of GDP per year. While development needs vary across countries, estimates suggest large spending needs for most ASEAN countries. Meeting them will require efforts on multiple fronts, including improvements in spending efficiency, tax capacity, and support from the private sector. For developing ASEAN countries, concessional financing from development partners will be required. The IMF continues to engage ASEAN countries in key areas as they pursue their SDGs. As called for in their mandates, ASEAN and the IMF both strive for economic growth and sustainable development through economic integration and collaboration among their member countries. The IMF has increased its engagement with ASEAN countries to support their policy efforts through its policy diagnostics, advice, and capacity development. ASEAN countries have also received support through IMF initiatives in strengthening revenue mobilization, building state capacity for infrastructure provision, pursuing economic and financial inclusion, addressing the challenges of climate change, strengthening economic institutions for good governance, and building statistical capacity. While fundamental reforms to improve sustainable development take time to bear fruit, there is evidence that efforts have started to pay off.